Timing, number, and type of sexual partners associated with risk of oropharyngeal cancer. Issue 7 (11th January 2021) - Drake, Virginia E.; Fakhry, Carole; Windon, Melina J.; Stewart, C. Matthew; Akst, Lee; Hillel, Alexander; Chien, Wade; Ha, Patrick; Miles, Brett; Gourin, Christine G.; Mandal, Rajarsi; Mydlarz, Wojciech K.; et al.
Abstract : Background: Case‐control studies from the early 2000s demonstrated that human papillomavirus–related oropharyngeal cancer (HPV‐OPC) is a distinct entity associated with number of oral sex partners. Using contemporary data, we investigated novel risk factors (sexual debut behaviors, exposure intensity, and relationship dynamics) and serological markers on odds of HPV‐OPC. Methods: HPV‐OPC patients and frequency‐matched controls were enrolled in a multicenter study from 2013 to 2018. Participants completed a behavioral survey. Characteristics were compared using a chi‐square test for categorical variables and a t test for continuous variables. Adjusted odds ratios (aOR) were calculated using logistic regression. Results: A total of 163 HPV‐OPC patients and 345 controls were included. Lifetime number of oral sex partners was associated with significantly increased odds of HPV‐OPC (>10 partners: odds ratio [OR], 4.3 [95% CI, 2.8‐6.7]). After adjustment for number of oral sex partners and smoking, younger age at first oral sex (<18 vs >20 years: aOR, 1.8 [95% CI, 1.1‐3.2]) and oral sex intensity (>5 sex‐years: aOR, 2.8 [95% CI, 1.1‐7.5]) remained associated with significantly increased odds of HPV‐OPC. Type of sexual partner such as older partners when a case was younger (OR, 1.7 [95% CI, 1.1‐2.6]) or having a partner who had extramarital sex (OR, 1.6 [95% CI, 1.1‐2.4]) was associated with HPV‐OPC. Seropositivity for antibodies to HPV16 E6 (OR, 286 [95% CI, 122‐670]) and any HPV16 E protein (E1, E2, E6, E7; OR, 163 [95% CI, 70‐378]) was associated with increased odds of HPV‐OPC. Conclusion: Number of oral sex partners remains a strong risk factor for HPV‐OPC; however, timing and intensity of oral sex are novel independent risk factors. These behaviors suggest additional nuances of how and why some individuals develop HPV‐OPC. Abstract : This comprehensive behavioral case‐control study of human papillomavirus (HPV)‐related oropharyngeal cancer reveals that oral sex and number of partners remain strong risk factors for HPV‐related oropharyngeal cancer. Measures of oral sexual behavior—including early age and intensity of exposure—are independent risk factors, suggesting that these behaviors may explain additional nuances of how and why some individuals develop HPV‐related oropharyngeal cancer.